Local Economic Development-Based on Farming Manufacture of Coconut Sugar in West Sei Kepayang District - Khairani Alawiyah Matondang; Agus Suman; Sasongko Sasongko; Putu Mahardika A.S. (Institute of Research and Community Service, University of Brawijaya)
The existence of coconut commodity abundance in the district of West Sei Kepayang of Asahan regency of North Sumatra province has not been utilized to the fullest. Though the potential of this commodity can be the basis of local economic development (LED). Of some its derivative products, coconut sugar has the economic potential to improve farmers welfare due to various advantages as well as a good market share prospect.This study aims to analyze the potential for the farm manufacture of coconut sugar to be used as a base of LED in the district of West Sei Kepayang. Data collected by survey method and then analyzed by descriptive quantitative by a financial feasibility analysis those are the Net Present Value (NPV), Net Benefit Cost Ratio (NBCR), Internal Rate of Return (IRR) and Payback of Period (PP) and by descriptive qualitative. The results of a financial feasibility analysis showed that the NPV is positive, NBCR is greater than one, the IRR is greater than the actual interest rate and PP can be restored in a relatively short time.Keywords: Local Economic Development, Coconut Sugar, Financial Feasibility Analysis.